Incident heart failure and the subsequent risk for progression to end stage kidney disease in South East Asian people with type 2 diabetes. (25th January 2023) - Liu, S; Liu, J J; Ang, K; Lim, S C
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Singapore National Medical Research Council grants: CSA-INV/0020/2017 and CS-IRG (MOH-000066) Background: Heart failure (HF) is a common but often unrecognized complication of type 2 diabetes (T2D). Both low eGFR and high albuminuria are strong risk factors for development of HF in diabetic population. However, data on the role of HF in long-term kidney disease outcome are sparse. Aim: We sought to study the risk for progression to end stage kidney disease (ESKD) after incident HF in multi-ethnic South East Asian people with type 2 diabetes. Participants and Methods: A total of 1, 756 individuals with type 2 diabetes recruited from a regional hospital were followed for a median of 7.3 (interquartile range 6.8-7.8) years. Incident HF was identified according to European Society of Cardiology 2016 criteria. HF was subtyped into preserved ejection fraction (HFpEF) and reduced ejection fraction (HFrEF) with ventricular ejection fraction (LVEF) cut-off at ≥50% and <50% respectively. Progression to ESKD was defined as patients with sustained eGFR <15ml/min per 1.73m2 with confirmation measurement 3 months apart, or on sustained dialysis for at least 3 months or death attributable to renal cause, whichever occurred first. The risk of progression to ESKD after HF was assessed using Cox proportional hazard models. Results: Average age of participants was 57±11 years with diabetes duration of 11 (IQR 4-15) years. There were 52% Chinese, 22% Malay and 26% Asian Indian in the study participants. We identified 113 incident HF events (65 HFpEF and 48 HFrEF) during 11, 869 patient-years (crude incidence rate 9.5 per 1000 patient-years). Individuals with HF occurrence were older, had a longer diabetes duration, higher body mass index, HbA1c and systolic blood pressure, and prevalent diabetic kidney disease (DKD). We identified 75 ESKD events in the follow-up (incidence rate 6.0 per 1000 patient-years) and 22 occurred after incident HF. Cox regression model showed that incident HF was associated with 7.4-fold (95% CI 4.5-12.2) unadjusted risk for progression to ESKD. The association of HF with subsequent risk for ESKD remained statistically significant (adjusted hazard ratio, HR 2.3, 95% CI 1.3-4.2) after adjustment for multiple clinical risk factors including baseline eGFR and albuminuria. Similar outcome was obtained when death attributable to non-renal cause was taken as a competing risk for ESKD. In a fully adjusted model, both HFpEF and HFrEF patients had a higher risk for progression to ESKD (adjusted HR 2.8, 95%CI 1.4-5.9, and 2.2, 95%CI 1.0-4.7, respectively), as compared to those with no HF events. The incidence rate of ESKD in patients with incident HF was 5.6 per 100 patient-years whilst in propensity score-matched patients without HF event, the rate was 2.1 per 100 patient-years. Conclusion: Incident HF is a strong independent risk factor for progression to ESKD in individuals with T2D. Our data highlight the importance for prevention, early diagnosis and treatment of HF to improve the renal outcomes in individuals with type 2 diabetes. Kaplan Meier plot Cox regression table